Kumba Building Rules Agitation Against (Colonial Letters and the Contact of Knowledges, 1947)
This file contains colonial letters on Kumba Building Rules and the contestations against
Keywords: Archives; Colonisation; Letters; Social norms; Discourse analysis; British Colonisation; Colonial Records; Kumba; Southern Cameroons; Postcolonial Heritage; Great Britain; Postcolonial Studies